PERANCANGAN MEDIA PROMOSI PT PETRONIKA SEBAGAI UPAYA PEMBENTUKAN CITRA PERUSAHAAN - Amaliah, Norma; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: PT Petronika is producing dioctyl phthalate (DOP) factory which was founded on September 14, 1983. Pros of PT Petronika this is the resulting product quality, use of eco environmentally production processes, and a good system. These advantages can reflect a positive image and become the deferensiation of its competitors. The problem of PT Petronika are havenât made promotional media can shape the image of the company. Design of media promotion of PT Petronika is expected to shape the corporate image, increase the consumers and the interests of investors to be able to cooperate with PT Petronika. This research uses research methods qualitative. Qualitative research is conducted with interviews, observation, documentation, and literary studies to obtain data that are used as a foundation in designing the design concept. Concepts in the design of media promotion of PT Petronika as the creation of the corporate image is "trusted quality". The Word trusted quality is taken to define the quality of the product produced by PT Petronika which is trusted and recognized by consumers domestic and foreign. It is evident from some of the recognition awards acquired PT Petronika and also havenât any complaints from loyal consumers. Give priority to the quality of the resulting product could be the deferensiation of product competitors. The concept is implemented in the strategy of creative and media strategy. The end result of this design is expected to make media promotions company that can reflect and more competitive.Â Â Keywords: Design, MediaÂ Promotions,Â Corporate Image.